Dramatic Clinical Response of Relapsed Metastatic Extramammary Paget's Disease to Trastuzumab Monotherapy. (27th March 2012) - Wakabayashi, S.; Togawa, Y.; Yoneyama, K.; Suehiro, K.; Kambe, N.; Matsue, H.
Abstract : We report the first case of 68-year-old Japanese woman with metastatic HER2-positive extramammary Paget's disease that showed the validity of trastuzumab monotherapy. We administered trastuzumab at a loading dose of 8 mg/kg i.v., followed by a 6 mg/kg maintenance dose every three weeks according to a protocol for HER2-positive metastatic breast cancers and a near-complete response was achieved after the tenth infusion. The patient experienced a moderate headache and flushing during the first infusion, but had no advanced effects during subsequent infusions with ibuprofen and d-chlorpheniramine maleate. Given the dramatic response, the patient has had 17 infusions of trastuzumab with no disease progression. Thus, trastuzumab has few side effects and is well tolerated for elderly patients. It may become a new choice of the adjubant therapy of this disease.